Pengaruh Citra Tubuh, Perilaku Makan, dan Aktivitas Fisik Terhadap Indeks Massa Tubuh (IMT) pada Remaja: Studi Kasus pada SMA Negeri 12 DKI Jakarta - Kusuma, Muhammad Ridwan Hadi; Krianto, Tri (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2018)
Background. "Thin is beautiful" is an erroneous understanding of body image that becoming a dream for every teenage girl. This is often the cause of problems, because to maintain her slimness and fear of becoming obese encourage teenagers to apply excessive dietary restrictions, so that their nutritional needs are not met which will be result in the occurrence of malnutrition. Objective. The aim of this studyis to determine the influence of body image against eating behavior and body mass index (BMI) among 10th and 11th grades 12th East Jakarta States Senior High School’s female students in 2014. Method. This study was conducted in April - May 2014, with cross sectional design, the study sample was 238 female students. Results. The results of this study using path analysis concluded that the presence of the influence of body image against BMI through eating behavior and physical activity, proved that the body image does not directly influence the IMT, but remains to be seen how eating behavior and physical activity undertaken by respondents. Therefore, efforts are required to empower our teenagers by challenging unhealthy beliefs they may have regarding weight, shape, and eating behavior. In addition, there should be regular nutrition counseling activities for teenagers with education material about body image and eating behavior, especially on a balanced diet and ideal body weight for teenage girls.